The speaker's ideal entertainments - Vickers, George M. (George Morley), 1841-1908; Peirce, Frances E. (Salt Lake City, UT : Project Gutenberg, 2023)
"The Speaker's Ideal Entertainments: For Home, Church and School" by George M. Vickers is a collection of recitals, dialogues, and dramas written in the late 19th century. This work serves as a comprehensive resource for those interested in elocution and performance, featuring a carefully curated selection of pieces that emphasize effective delivery and gesture. The book includes annotations and hints on dramatic poses to aid both novices and seasoned performers. The opening of this work presents an introduction that outlines its purpose and structure, emphasizing the importance of elocution in delivering recitations. Vickers expresses confidence in the value of this compilation as a solution to the needs for suitable dramatic material, asserting that the selections are unique, including many new pieces, and are well-suited for educational and entertainment settings. The initial section highlights the book's features, such as the notation of gestures, which should help reciters enhance their performances by incorporating expressive movement effectively. Each piece, curated for its elocutionary merits, invites readers and performers alike to explore the art of storytelling and dramatic presentation. (This is an automatically generated summary.)
Release date is 2023-05-12
Carol Brown, Tim Lindell, Chuck Greif, Peter Vachuska, Jude Eylander and the Online Distributed Proofreading Team at https://www.pgdp.net
Keywords: Elocution; Recitations